Analisis Implementasi Kebijakan Pencegahan dan Penanggulangan Stunting Terintegrasi Dalam Program Gerakan 1000 HPK di Puskesmas Pagar Jati - Febiayu Rahmanda; Fitriani Pramita Gurning (PubHealth Jurnal Kesehatan Masyarakat, 2022)
The results of the 2018 Riskesdas, stunting toddlers in Indonesia reached 30.8%. SSGBI data in 2019, stunting under five in Deli Serdang Regency reached 30.97%. Stunting toddlers at the Pagar Jati Health Center continues to increase, in 2018 there were 0 cases, in 2019 there were 37 cases, and in 2020 there were 51 cases of stunting toddlers. This study aims to analyze the implementation of integrated stunting acceleration and prevention policies in the First 1000 Days of Life (HPK) Movement Program in the Pagar Jati Public Health Center, Deli Serdang Regency. The research method is descriptive qualitative which was carried out from May to November 2021. Informants in this study were the Head of Pagar Jati Health Center, Community Nutrition Coordinator, Maternal and Child Health Coordinator, Health Promotion Coordinator, health cadres, and mothers of toddlers. Data was collected by means of observation, in-depth interviews and document studies. The results showed that the input elements, namely the availability of human resources and infrastructure in the implementation of the 1000 HPK program at the Pagar Jati Health Center were still inadequate. In the process, the antenatal care (ANC) examination was carried out well, while monitoring the growth of children under five, giving immunizations, providing additional food, and counseling on stunting was quite well done. In the output element, 8 out of 10 program achievement indicators have reached the target. It is necessary to increase the maximum stunting prevention program at the Pagar Jati Health Center, to increase the completeness of facilities and infrastructure for stunting prevention.